2008
DOI: 10.2109/jcersj2.116.291
|View full text |Cite
|
Sign up to set email alerts
|

Grain size dependence of electrical properties of Gd-doped ceria

Abstract: A Gd-doped ceria powder (GDC, Ce 0.8 Gd 0.2 O 1.9 ) prepared from an oxalate precursor was hot-pressed at 1173-1273 K in Ar atmosphere and annealed in air at 1273-1473 K to control the bulk density and grain size. Complex impedance of GDC of the microstructures of 0.29-5.6 mm average grain size and 95-98 theoretical density were measured at 573-1073 K in air in the frequency range from 100 Hz to 2 MHz. The bulk conductivity (s i (b)) was independent of the grain size and the activation energy for the migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
4
17
2
Order By: Relevance
“…While the ratio was not influenced by the temperature, the ratio increased with decreasing the grain size. This result was agreement with that of the literature [1] which reported that the ratio was 0.3 and 0.5 for GDC samples with a grain size of 510 and 290 nm, respectively.…”
Section: Ac Impedancesupporting
confidence: 93%
See 2 more Smart Citations
“…While the ratio was not influenced by the temperature, the ratio increased with decreasing the grain size. This result was agreement with that of the literature [1] which reported that the ratio was 0.3 and 0.5 for GDC samples with a grain size of 510 and 290 nm, respectively.…”
Section: Ac Impedancesupporting
confidence: 93%
“…Figures 3 and 4 show the complex impedance plots for the GDC samples sintered using the SPS process and the normal sintering process, respectively. The shape of the obtained complex impedance plot was similar to that reported in the literature [1]. That is, (1) the complex impedance plot obtained below 350 ºC showed three , k: constant).…”
Section: Measurement Of Electrical Conductivitysupporting
confidence: 86%
See 1 more Smart Citation
“…The calculation is based on a single grain-boundary thickness of 3 nm and a relative dielectric constant of 1.72. 14) These results suggest that the arc in the low-frequency range represents the charge transfer characteristics at the electrodes. The ohmic resistance increased from 1.95 ³ in the case of no added GDC to 5.3 ³ in the cases of electrodes with 10 and 50 mass % GDC.…”
Section: ¹mentioning
confidence: 88%
“…conductivity at the higher temperature with decreasing grain size may be attributed to the increase in the fraction of the low conductivity grain boundary. 23) On the other hand, the increase in electrical conductivity at the lower temperature with decreasing grain size may be due to the increase in the fraction of the high conductivity cubic phase. This suggestion comes from the results of the X-ray diffraction measurement which indicated the cubic phase for the ScSZ with a smallest grain size fabricated by SPS process, and the thermal expansion measurement which showed the hysteresis curve due to the phase transition for the ScSZ with larger grain size heated at 1300 or 1500°C.…”
Section: Introductionmentioning
confidence: 99%